Media sosial dan perilaku pembelian impulsif: Peran motivasi belanja hedonis dan orientasi belanja - Irene Deborah; Yevis Marty Oesman; R. Thomas Budhyawan Yudha (Jurnal Manajemen Maranatha, 2022)
The high number of internet users and the development of social media such as Instagram and Tiktok currently one of the factors in the developmeny of high consumption of fast fashion products that are slowly changing people’s lifestyle. Consumers make undirected purchases which result in increased hedonic motivation and shopping orientation. This study to examine whether social media affects impulse buying behavior through hedonic shopping motivation and shopping orientation in purchasing fast fashion products. This study uses descriptive and verification quantitative research methods using structural equation model (SEM) analysis which is processed using SmartPLS on 239 respondents of generation Y and Z in West Java. The result showed that (1) social media have a positive and significant effect on impulsive buying behavior, (2) social media have a positive and significant effect on hedonic shopping motivation, (3) social media have a positive and significant effect on shopping orientation, (4) hedonic shopping orientation have a positive and significant effect on impulsive buying behavior, (5) shopping orientation have a positive and significant effect on impulsive buying behavior, (6) positive and significant hedonic shopping motivation and shopping orientation able to mediate the effect between social media on impulsive buying behavior. This study shows that social media usage can influence impulse buying behavior, especially in buying fast fashion products. Hedonic shopping motivation and shopping orientation can be influenced by social media and affect impulsive buying behavior so that requires attention for producers in selling which products will be sold or not. On other hand, consumers also need to pay attention to products that they are going to buy so that their purchasing patterns are more focused.